Sexual responses to intrauterine stress: body and brain growth - Dressino, Vicente (2002)
The aims of this work were to analyse body and brain growth as produced by deficiencies in the uteroplacenta bllood supply,and to evaluate sexual responses to intrauterine stress. Intrauterine growth retardation(IUGR) was experimentally induced in pregnant rats by partial obstruction in both uterine vessels at 1,7 and 14 gestational days. The dysfunctions in the placental circulation retarded both somatic and cerebral growth, depending on the period of gestational stress and the sex. Brain weight had a relatively greater resistance than body weight, which is called a "brain sparing" mechanism. The body and brain sexual dimorphism in control pups was inhibited in IUGR pups. This study shows that prenatal stress exposition might modify growth and sexual dimorphism at birth.